Stress Corrosion Cracking of X80 Steel in the Presence of Sulfate-reducing Bacteria. Issue 4 (April 2015) - Wu, Tangqing; Yan, Maocheng; Zeng, Dechun; Xu, Jin; Sun, Cheng; Yu, Changkun; Ke, Wei
<x xml:space="preserve">Abstract</x> The systematic laboratory studies on the roles of sulfate-reducing bacteria (SRB) in the stress corrosion cracking (SCC) susceptibility of X80 steel subjected to cathodic potential have been conducted in a near-neutral pH soil solution by slow strain rate tests. The cathodic potential and SRB increase individually the SCC susceptibility of the steel in the soil solution. The positive role of the SRB activities in SCC susceptibility depends on the prolongation of pre-incubation time, and the SCC susceptibility of the steel increases under more negative potentials. What's more, the applied potentials and the presence of SRB work together in promoting the SCC susceptibility of the steel. But, the combined action becomes limited with decreasing cathodic potentials. The relationships between the plasticity loss and the permeable hydrogen concentration were established for the steel in the soil solution, regardless of under open circuit potential or cathodic potentials, in both the sterile and SRB inoculated conditions. The relationships are practically significant for the selection of safe cathodic protection (CP) potentials in the presence of SRB in soil environment.